Lifestyle modification based on cluster cardiovascular risk assessment reduced the risk of sleep apnea. (14th October 2021) - Guo, Y; Zhang, H; Lip, G Y H; ,
Abstract: Background: Sleep apnea is associated with cardiovascular events, nonetheless, the early concern for multi-risk factor management, complied with guideline-based clinical care pathways, is limit. Objective: The present study aimed to investigate the impact on the burden of sleep apnea with lifestyle and physical activity modification based on cardiovascular cluster risk factors assessment, supported by a mobile health and wearable devices technologies. Methods: The adult subjects aged over 18 years were enrolled in China between March 2, 2020 and August 4, 2020, who used a smart phone application "IamHealthy", to assess the CV risk profile, including weight/activity, diet (the quality of diet was assessed using Alternative Healthy Eating Index, AHEI-2010), psychological status, sleep apnea, cardiac rhythm, blood pressure, blood lipid, diabetes. Once the subjects had compatible smart devices (Huawei Technologies Co., Ltd., Shenzhen, China), they achieved photoplethysmography (PPG)-based sleep apnea monitoring. The healthy lifestyle score (five aspects: diet, smoking, physical activity, alcohol consumption, and Body Mass Index) were calculated and a 3-month personalized App-based lifestyle and physical activity package was proposed for those with sleep apnea. The change on risk of sleep apnea monitored were evaluated. Results: There were 775 subjects (mean age 48 years old, standard deviation, SD, 14, 90.1% male) with the "IamHealthy" App and 487 subjects (mean age 46 years old, standard deviation, SD, 13, 94.4% male) for sleep apnea monitoring with smart devices. Among these subjects, there were 42.3% subjects with overweight, 13.2% with obese; 44.3% with poor quality of healthy diet (AHEI scores <66), 40.0% with inactive physical activity of <1 time/week. The reported depression (Patient Health Questionnaire, PHQ-9 ≥5) and the anxiety (Generalised Anxiety Disorder, GAD-7 scale ≥5) were 41.2% and 62.5%, respectively. Only 22.4% subjects remained healthy lifestyle with over three low risk lifestyle scores. Dietary Approaches to Control weight (61.6%), to Stop Hypertension (24%), and Mediterranean dietary (5%); Physical activities to control the weight (84.2%), control blood pressure (8.5%), and CV prevention (6.8%) were commonly proposed. For subjects using IamHealthy to monitor sleep apnea after matching PPG -smart devices on baseline, the proportion of high-risk of sleep apnea decreased over time (baseline, 1 mon, 3 mons, and 6 mons, 60.67%, 47.25%, 44.12%, and 34.19%, p<0.001, Figure). Conclusions: Lifestyle modification based on cluster cardiovascular risk assessment reduced the high-risk sleep apnea. Funding Acknowledgement: Type of funding sources: None.